Validating South Sudan as a Center of Origin for Coffea arabica: Implications for Conservation and Coffee Crop Improvement - Krishnan, Sarada; Pruvot-Woehl, Solene; Davis, Aaron P.; Schilling, Tim; Moat, Justin; Solano, William; Al Hakimi, Amin; Montagnon, Christophe (Frontiers in Sustainable Food Systems, 2021)
Cultivated Arabica coffee outside Ethiopia is plagued by low genetic diversity, compromising disease resistance, climate resiliency and sensory potential. Access to the wider genetic diversity of this species may circumvent some of these problems. In addition to Ethiopia, South Sudan has been postulated as a center of origin for Arabica coffee, but this has never been genetically confirmed. We used simple sequence repeat (SSR) markers to assess the genetic diversity of wild and cultivated populations of Arabica coffee from the Boma Plateau in South Sudan, against farmed accessions (of wild origin) from Ethiopia, Yemen, and global cultivars. Our results not only validate Boma Plateau as part of the natural distribution and as a center of origin for Arabica coffee but also indicate that wild populations in South Sudan are genetically distinct from Ethiopian Arabica. This newly identified genetic diversity within Arabica could have the potential for crop improvement through selection and use in breeding programs. Observations and analyses show that the extent and health of the wild population of Arabica in South Sudan have declined. Urgent action should be taken to conserve (in situ and ex situ) the unique, remaining genetic diversity of wild Arabica populations in South Sudan.